A Model of the Degrading Solute Transport in Porous Media based on the Multi-Stage Kinetic Equation - Khuzhayorov, Bakhtiyor; Fayziev, Bekzodjon; Sagdullaev, Otabek; Makhmudov, Jamol; Saydullaev, Usmonali (Engineering, Technology & Applied Science Research, 2025)
A mathematical model of solute transport in porous media with two adsorption zones was developed, incorporating balance and kinetic equations, and initial and boundary conditions. The model was enhanced to account for multistage deposition kinetics in both adsorption zones, and numerical methods were employed to solve the problem. An algorithm using the finite difference method was presented as a solution. Computer experiments were conducted to ascertain the effect of different parameters of the model on solute transport, and the results of the study were analyzed. The primary focus of this study is to assess the impact of parameters within the kinetic equations on the transport process. These parameters are crucial in determining the intensity of adsorption during various stages of the process. The findings of this study demonstrate that multistage deposition kinetics significantly influences both the transport and adsorption processes. Furthermore, the presence of two distinct intensity areas in the concentration profile of the adsorbed substance is observed. This phenomenon is attributed to the effects of multistage kinetics.